Exploring the Use and Development of Drama in Education in Elementary and Secondary Ethics and Rule of Law Course - Chen, Zhirui (Transactions on Social Science, Education and Humanities Research, 2024)
Drama in Education (DIE) is becoming more and more important in the context of the development requirements of the country’s soft power. As an important criterion of national soft power, Drama in Education (DIE) is gradually being integrated into all aspects of the school community. By bringing Drama in Education to Ethics and Rule of Law classes for primary and secondary school students, integrate the two. And through the practice of a combination of dots and lines to promote educational theater, receive a good response. The significance of Drama in Education is to energize the rigid classroom, to make it fun, to stimulate the potential of the classroom, and to improve the efficiency of the classroom for the students. Drama in Education breaks the traditional classroom model and makes the classroom content more colorful. However, the development of Drama in Education continues to progress slowly and steadily against all odds. Advancing Drama in Education on the Road to Transforming the Ethics and Rule of Law Classes, teachers in primary and secondary schools, as well as those responsible for leading relevant departments, have a long way to go. It is indisputable that Drama in Education plays an integral role in the Ethics and Rule of Law classroom for elementary and middle school students. It believes that even without a very strong foundation, China’s educational theater will thrive in the future.